Challenges and Future Perspectives of Supercapacitor Materials: Mini Review - Sa’adu, Lawal; Abdullahi, Ibrahim; Bello Muhammad, Samaila; Bala Isah , Adamu; Azman Hashim , Mohd; Yusuf, Yahaya (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Supercapacitors (SCs) formed an integral part of the contemporary energy storage systems thanks to their unique traits of power delivery and charge storage capabilities coupled with long cyclic stability (˃105). In its basic form, a Supercapacitor (SC) consists of two separated electrodes impregnated with an electrolyte. The performance of SC is largely a function of the chosen electrode-electrolyte materials. The choice of the materials depends on the prevailing conditions at hand and is always at a tradeoff between certain merits and de-merits. Herein, we reviewed the different types of SC materials (both electrodes and electrolytes) with emphasis on the challenges associated with each. This will create an avenue in determining the direction and future perspective of SC materials.